2008
DOI: 10.1177/112067210801800329
|View full text |Cite
|
Sign up to set email alerts
|

Needle-Shaped Deposits on Retinal Surface in a Case of Ocular Amyloidosis

Abstract: In this case, OCT showed needle-shaped deposits perpendicular to the retinal surface. Special staining with Congo red revealed the deposit to be amyloid deposition. Immunohistochemical staining suggested light chain-related amyloidosis. Vascular obstructive lesions and neovascular glaucoma secondary to retinal vascular damage in amyloidosis warrant particular attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
3
8
0
Order By: Relevance
“…This observation may be attributed to the fact that most of these deposits were removed during vitrectomy. Other findings such as retinal hemorrhages that have been reported previously [9][10][11] were absent in our case. These deviations suggested clinical heterogeneity of vitreous amyloidosis.…”
Section: Mutation Analysissupporting
confidence: 75%
See 2 more Smart Citations
“…This observation may be attributed to the fact that most of these deposits were removed during vitrectomy. Other findings such as retinal hemorrhages that have been reported previously [9][10][11] were absent in our case. These deviations suggested clinical heterogeneity of vitreous amyloidosis.…”
Section: Mutation Analysissupporting
confidence: 75%
“…It was previously reported that the needle-shaped deposits perpendicular to the retinal surface are oriented towards the vitreous on the OCT. 11 These deposits were extensively found on the macula in the reported literature; 11 however, they were limited to the perifoval region in our case. This observation may be attributed to the fact that most of these deposits were removed during vitrectomy.…”
Section: Mutation Analysismentioning
confidence: 53%
See 1 more Smart Citation
“…Ophthalmic manifestations of systemic amyloidosis include deposition into the eyelid, conjunctiva, lacrimal gland, vitreous, all layers of the retina, and in vessels of the retina and choroid. [3][4][5][6][7][8] We present four patients with systemic amyloidosis (one primary and three secondary) and renal failure, which demonstrate consistent and characteristic chorioretinal findings with multimodal imaging.…”
mentioning
confidence: 99%
“…Glaucoma as an independent condition in vitreous amyloidosis or concurrently developed complication, can be managed with filtering surgery at the time of vitrectomy or at any time postoperatively. [43][44][45][46][47][48][49][50][51][52][53][54][55]…”
Section: Vitreoretinal Involvementmentioning
confidence: 99%